Penerapan Metode Discovery Learning untuk Meningkatkan Hasil Belajar IPAS dan Kreativitas Siswa Kelas IV MIT Insan Cendikia Makassar - Sadrianti, Sadrianti; Supriadi, Supriadi; Nurdiansyah, Erwin; Mulyadi, Mulyadi; Afni, Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to describe the implementation of the Discovery Learning model to enhance students’ learning outcomes and creativity in the IPAS subject. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The participants were 20 fourth-grade students at MIT Insan Cendikia Makassar. Data were collected through tests, observations, and assessment sheets, and analyzed using a qualitative descriptive approach. The findings revealed that the application of the Discovery Learning model effectively improved students’ learning outcomes and creativity. The average learning outcome score increased from 79.55 in Cycle I to 84.33 in Cycle II, while the level of student creativity rose from 64.25% to 89.5%. Furthermore, 95% of students achieved scores above the Learning Objective Achievement Criteria (KKTP). These results demonstrate that the Discovery Learning model is effective in fostering both academic achievement and creative skills among students in the IPAS subject.